Cross-Disciplinary Physics and Related Areas of Science and Technology : A Back-Gated Ferroelectric Field-Effect Transistor with an Al-Doped Zinc Oxide Channel. (4th February 2015) - Jia, Ze; Xu, Jian-Long; Wu, Xiao; Zhang, Ming-Ming; Liou, Juin-J.
Abstract: We report a back-gated metal-oxide-ferroelectric-metal (MOFM) field-effect transistor (FET) with lead zirconate titanate (PZT) material, in which an Al doped zinc oxide (AZO) channel layer with an optimized doping concentration of 1% is applied to reduce the channel resistance of the channel layer, thus guaranteeing a large enough load capacity of the transistor. The hysteresis loops of the Pt/PZT/AZO/Ti/Pt capacitor are measured and compared with a Pt/PZT/Pt capacitor, indicating that the remnant polarization is almost 40 μC/cm 2 and the polarization is saturated at 20 V. The measured capacitance-voltage properties are analyzed as a result of the electron depletion and accumulation switching operation conducted by the modulation of PZT on AZO channel resistance caused by the switchable remnant polarization of PZT. The switching properties of the AZO channel layer are also proved by the current-voltage transfer curves measured in the back-gated MOFM ferroelectric FET, which also show a drain current switching ratio up to about 100 times.